(untitled) (Journal of the College of Basic Education, 2022)
The current paper analyzes Caryl Churchill’s representation of the stereotype image of women in Top Girls (1982). The play shows how women in their strife to fight the oppression of men throughout history, they have reached a level of power and freedom which are used to control their gender without compassion. Marlene, the central character of this play, is a woman who adopted masculine qualities to the extreme. To mountain the ladder of success to its top, Marlene sacrifices her child, family, and love. Also, the play presents the silenced women who are oppressed, dependent and sacrificed the chance to be independent and free. Moreover, the paper investigates the views of different classes, particularly the status of working class, towards the policies of the first female prime minister of the UK, the Iron Lady, Margaret Thatcher. Keywords: Caryl Churchill, Top Girls, Margret Thatcher, Stereotype, Patriarchy, Class, and Oppression